2014
DOI: 10.1109/tps.2014.2350533
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Soil Treated With Ozone Generated by Surface Discharge

Abstract: Chemical contamination in plants, soil, and ground water has become serious by overuse of pesticides and nitrogen fertilizers in agriculture. We propose the use of ozone generated by atmospheric pressure plasma for soil disinfection as one of the plasma applications into agriculture. Because ozone has strong oxidation potential to decompose organic substances in soil, it is considered to be one of the candidates as potential alternative to both pesticide and nitrogen fertilizer. In this paper, fundamental stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 22 publications
2
10
0
1
Order By: Relevance
“…Microbial communities in bulk soil and associated with plant roots are known to be responsible for N cycling, significantly impacting plant growth dynamics and soil fertility, where microbially catalyzed transformations regulate biologically available N through exchange with the atmosphere via N 2 fixation and denitrification processes and loss by nitrate leaching through the action of nitrifying bacteria (Figure 4). [ 157 ] Although direct plasma treatment of soils is known to impact N present in soils through two separate mechanisms, [ 158–162 ] (1) chemical alteration of N species and (2) modification of microbial community structures responsible for biotransformation of N species, an understanding of the effects on N species levels in soils resulting from irrigation with PTW is more limited. A study by Mitsugi [ 158 ] demonstrated that O 3 treatment, produced by an SDBD and allowed to diffuse into the soil (andosol and compost), resulted in an increase from 90 to 200 mg kg −1 for NO 3 − –N and a decrease of NH 4 + ‐N from 200 to 20 mg kg −1 at the soil surface (within 5 cm) due to N species in the soil reacting with O 3 (Table 6).…”
Section: Soil and Microbiome Impactsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbial communities in bulk soil and associated with plant roots are known to be responsible for N cycling, significantly impacting plant growth dynamics and soil fertility, where microbially catalyzed transformations regulate biologically available N through exchange with the atmosphere via N 2 fixation and denitrification processes and loss by nitrate leaching through the action of nitrifying bacteria (Figure 4). [ 157 ] Although direct plasma treatment of soils is known to impact N present in soils through two separate mechanisms, [ 158–162 ] (1) chemical alteration of N species and (2) modification of microbial community structures responsible for biotransformation of N species, an understanding of the effects on N species levels in soils resulting from irrigation with PTW is more limited. A study by Mitsugi [ 158 ] demonstrated that O 3 treatment, produced by an SDBD and allowed to diffuse into the soil (andosol and compost), resulted in an increase from 90 to 200 mg kg −1 for NO 3 − –N and a decrease of NH 4 + ‐N from 200 to 20 mg kg −1 at the soil surface (within 5 cm) due to N species in the soil reacting with O 3 (Table 6).…”
Section: Soil and Microbiome Impactsmentioning
confidence: 99%
“…A second study by Mitsugi et al [ 159 ] also showed an increase in NO 3 − –N (a change from 0.25 to 9.0 mg kg −1 ) upon treatment of Andosol soil using a similar discharge; however, in this case, NH 4 + –N levels also increased with O 3 treatment (an increase from 1 to 50 mg kg −1 ). [ 159 ] A third study by Mitsugi et al [ 164 ] reported an increase in NO 3 − –N and NH 4 + ‐N in response to soil O 3 treatment of 50−90 mg kg −1 and 5−15 mg kg −1 . Furthermore, treatment impacted the seed germination of Komatsuna, radish, and spinach differently.…”
Section: Soil and Microbiome Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the first therapeutic application for the purification of blood was reported in 1870 (Grootveld et al, 2004). Due to its high oxidation potential, several studies and applications have been performed using ozone such as water, soil and waste treatment (Ebihara et al, 2012;Mitsugi et al, 2014;Rice, 2012), surface treatment of polymeric materials (Walzak et al, 1995), industrial production with special use in food industry (Varga and Szigeti, 2016), health care, among others. Moreover, O 3 is considered an effective sterilant for various microorganisms.…”
Section: Evaluation Of Disposable Medical Device Packaging Materials mentioning
confidence: 99%
“…Elas direcionam para aplicações na área de saúde como cicatrização de feridas, coagulação sanguínea, desinfecção de cárie dentária e alteração de funções de células de mamíferos com potencial para novas terapias de cancro [13][14][15][16][17]. Na agricultura pode ser utilizado para estimular o crescimento de plantas e reduzir patógenos, germinação de sementes, descontaminação de superfícies biologicamente ativas de frutos e descontaminação pós-colheita [18][19][20][21][22][23]. Também na área ambiental, onde pode ser utilizado para descontaminação de ambientes, líquidos e sólidos, tratamento de água, degradação de corantes, entre outros [24,25].…”
Section: Introductionunclassified